MOVEMENT PROJECTION OF AIRCRAFT PASSENGERS AT HALIM PERDANA AIRPORT - Yulyanti, Anita (Institut Teknologi Dirgantara Adisutjipto, 2021)
Air transportation is increasingly in demand.. Airports as a gathering place for passengers must be prepared to face this increase in the number of aircraft passengers.This increase in airplane passengers certainly affects and is influenced by various socio-economic factors, including: population, number of hotels, number of tourists, GRDP (Gross Regional Domestic Product), and number of train passengers. Halim Perdana Kusuma Airport could be considered as new airports in Indonesia because it has only been used for commercial flights for 7 years starting from opening for public flights in 2014. This airport has visually increased the number of passengers each year so it is suitable as an object of research. Calculation of the estimated increase in airplane passengers at the airport can be done using a multiple linear regression method, while to find out how much influence the size of the increase in airplane passengers and socio-economic factors can use the correlation coefficient search